An update on the status of breast cancer screening in Brazil after the covid-19 pandemic - Jordana de Faria Bessa; Guilherme Novita; Ruffo Freitas-Junior (Universidade de São Paulo, 2022)
ABSTRACT We have previously reported the impact of covid-19 pandemic on breast cancer screening, in Brazil: among women aged 50-69 years, mammography attendance decreased by 42% in public healthcare (SUS), comparing 2019 and 2020. In this short communication, we wish to present: a) an update of the number of mammograms performed, in 2021; b) an exploratory analysis of the characteristics of the screened population between 2019 and 2021. A total of 1.675.307 mammograms were performed in 2021, nearly 15% lower than pre-pandemic levels. Almost a third, 29.5% of them, had intervals greater than three years. In accordance with our previous study, the number of patients with palpable lumps on physical exam increased. The consequences of postponing breast cancer screening during the pandemic are still uncertain. Unfortunately, as of December 2021, screening attendance has not resumed. On the contrary, our results show an increase in the fraction of women with mammography delayed beyond three years.